The comparison of physicochemical and bioactivity properties of different nanoparticles modified calcium silicate-based cement - Silsupa Saingern; Naruporn Monmaturapoj; Chanakarn Sinsareekul; Porawit Kamnoedboon; Thanaphum Osathanon; Murali Srinivasan; Pavena Chivatxaranukul; Thawanrat Singthong; Chalermkwan Makornpan; Dusit Nantanapiboon (BMC Oral Health)
Abstract Background To investigate the effects of adding ZrO₂, TiO₂, and two sizes of hydroxyapatite (HAP) nanoparticles on the physicochemical and bioactivity properties of calcium silicate-based cement (CSC). Methods MTA, PC, and nanoparticle-modified groups (5% and 10% n-ZrO₂, n-TiO₂, n-HAP1, n-HAP2) were evaluated for setting time, compressive strength (1, 7, 14 days), solubility (14 days), and bioactivity. Setting time and compressive strength followed ISO 9917–1:2007, solubility followed a modified ISO 6876:2012, and bioactivity was analyzed using SEM–EDS. Results All groups showed significantly reduced setting times (p < 0.001) compared to MTA and PC, with 10% n-HAP1 showing the greatest reduction. Compressive strength increased over time in all groups except 5% and 10% n-ZrO₂, which remained stable (p > 0.05). MTA had the highest strength at 14 days. MTA’s solubility was higher than PC’s (p < 0.001). All groups, except 10% n-TiO₂, 5% and 10% n-HAP1, showed increased solubility vs. MTA (p < 0.003); all exceeded PC (p < 0.001). SEM after 1 day showed spherical apatite structures, which thickened by days 7 and 14. EDS confirmed Ca/P ratios similar to controls. Conclusions All nanoparticles accelerated the setting time, and only ZrO₂ nanoparticles enhanced early strength. Despite increased solubility, all values remained within acceptable limits. All groups demonstrated bioactivity potential.